Beauty Myths and Consumer Culture in Indonesian Chick-lit Novel - Tania Intan; Nur Afifah Vanitha Binti Abdullah (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2021)
Abstract. The discourse on women’s beauty and femininity are inseparable from the patriarchal cultural construction. Women are to constantly strive to achieve a standard, that is known as ‘beautiful’ to men. The purpose of this research was to study the myth of beauty and consumer culture in a ‘chick-lit’ novel entitled Beauty Case by Icha Rahmanti. Data for this study was gathered from fundamental research that used a qualitative research design. This study utilized the notion of beauty in the various context presented by Wolf and the interpretation of beauty in marketing and colonial discourse raised by Priyatna, as it’s a theoretical framework. Wilson and Wolby’s idea of consumer culture was also employed to examine female consumer culture in this novel. The finding of this study is that the myth of beauty in Beauty Case revolves around profession, culture, and sexuality. This study also concludes that the consumer culture of the main and other female characters in this novel is very much influenced by the myth of beauty constructed by men. The female characters constantly try to look young and seek recognition from men in matters regarding their appearance. Besides that, Rahmanti’s female characters also always try to gain the approval of their deeds from their society.   Keywords: Myths of Beauty, Consumer Culture, Chick Lit, Beauty Case